Association between anthropometric measurements and lipid profile in newly detected hypertensive patients at a tertiary hospital in Bangladesh - Jishu Deb Nath; Rajat Sanker Roy Biswas (Journal of Indian College of Cardiology, 2020)
Introduction: Hypertension (HTN) is an important public health problem worldwide and causing global disease burden contributing as cardiovascular diseases, cerebrovascular disease (stroke), and end-stage renal disease and marked disability. Objectives: The objective was to investigate the correlation between anthropometric indices and dyslipidemia relating to newly diagnosed HTN and compare with normotensive individuals. Materials and Methods: A cross-sectional comparative study of 131 patients splitting two groups comprising 65 hypertensive patients as case and 66 normotensive patients as control underwent in a tertiary hospital. Different anthropometric indices and fasting lipid profile were evaluated between two groups with the help of SPSS software. Results: Among 131 patients, the mean ± standard deviation (SD) of systolic blood pressure (SBP) was 155.9 ± 9.18 in case group and 124.6 ± 22.06 in control group (P < 0.5) and diastolic pressure was 96.70 ± 6.10 in case group and 78.45 ± 6.98 in control group (P < 0.05). The mean ± SD body mass index was 24.23 ± 3.3 in case group and 22.13 ± 2.92 in control group (P < 0.05). Serum triglyceride was 251.13 ± 85.9 in case group and 256.5 ± 73.5 in control group (P < 0.05). Total cholesterol (TC) and low-density lipoprotein (LDL) were 230.2 ± 44.53 and 150.78 ± 32.9 in case group and 166.27 ± 30.45 and 98.9 ± 20.15 in control group (P < 0.05). Strong-positive correlation was found between high SBP and LDL (r = 0.517), high diastolic blood pressure (DBP) and LDL (r = 0.560), and high DBP and TC (r = 0.514). Conclusion: Anthropometric measures and lipid profile are the important tools should be emphasized early to diagnose HTN.